All joy and no fun : the paradox of modern parenthood - Senior, Jennifer (New York, NY : Ecco, an imprint of HarperCollins Publishers, 2015)
Thousands of books have examined the effects of parents on their children. In asking, what are the effects of children on their parents, the author analyzes the many ways in which children reshape their parents' lives, whether it's their marriages, their jobs, their habits, their hobbies, their friendships, or their internal senses of self. She argues that changes in the last half century have radically altered the roles of today's mothers and fathers, making their mandates at once more complex and far less clear. Recruiting from a wide variety of sources, she dissects both the timeless strains of parenting and the ones that are brand new, and then brings her research to life in the homes of ordinary parents around the country. The result is an unforgettable series of family portraits, starting with parents of young children and progressing to parents of teens. She follows these mothers and fathers as they wrestle with some of parenthood's deepest vexations and luxuriate in some of its finest rewards. Here she makes us reconsider some of our culture's most basic beliefs about parenthood, all while illuminating the profound ways children deepen and add purpose to our lives. By focusing on parentHOOD, rather than parentING, the book is original and essential reading for mothers and fathers of today, and tomorrow. -- From publisher description.
Drawing on a vast array of sources in history, sociology, economics, psychology, philosophy, and anthropology, a journalist challenges basic beliefs about parenthood while revealing the profound ways children deepen and add purpose to life.
Autonomy -- Marriage -- Simple gifts -- Concerted cultivation -- Adolescence -- Joy.
Originally published as hardcover: 2014.
Includes bibliographical references and index.
Keywords: Parenthood; Children; Parent and child; Child; Parent-Child Relations; Parents